(3WHbGJ GdTGaYjI GdcHQis - (3YHO GdhgGH Hf Ydj Hf YHO GdcGaj GdSHcj, CHh fUQ , JGL GdOjf , J (B771 (3g` s
(3ChdgG (B:s
(3bGd SjOfG GdSHci GdMeO ddg fMeOg hfSJYjfg MOKfG CHj GdTjN GdEeGe YdjfG ef daXg bGd GeG GHf GdSbWi jYfi eMeO YHO GdYXje s
(3BNQgG (B:s
(3hfGH ai GdbVGA HOeTb Yf bGVi eUQ hGdTGe CHj GdMSf Ydi Hf GdfYeGf Jhai SfI NeS hSYjf hKdKeGFI Je GdLRA GdChd HMeO Gddg hYhfg s
(3HBNQgG eWGYdI dYdi Hf YeGO GdOjf GdTGaYi SfI (B947s
(3HgG fXGe GdJYbjHIs
(3efbhdI ef fSNI bQCgG GHf MLQ GdYSbdGfis
(3hHChd GdfSNI Jedc dGHf bGVi YLdhf s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B184 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B6 - (3U (B225s
Keywords: (3GdJGQjNs